Mitral Valve Endocarditis due to Lactobacillus - Patrick Groga-Bada; Iris I. Mueller; Federico Foschi; Meinrad Gawaz; Christian Eick (Case Reports in Medicine)
Lactobacillus species are Gram-positive, facultative anaerobic, rod-shaped bacteria. They belong to the lactic acid bacteria group and are also known as a usual part of the normal flora of the gastrointestinal tract as well as of the urinary and genital tracts. They are an infrequent human pathogen but can induce several infections such as bacteremia and infectious endocarditis. We report the case of an 81-year-old woman with Lactobacillus bacteremia and mitral valve endocarditis as well as splenic abscesses.